Elastomer material of drag chain wire and preparation method of elastomer material

By using specific formulas and preparation methods to form a coordination crosslink network structure, the problems of low wear resistance and tensile strength of existing materials when used in various environments are solved, and high and low temperatures are significantly improved performance stability and service life.

CN119320543AInactive Publication Date: 2025-01-17SHENZHEN BAOYANG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410995327.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When used in various environments, existing drag chain wire materials have problems such as wear resistance, low tensile strength and large loss of performance under high and low temperature differences.

Method used

Used from copolymerized polypropylene, hydrogenated styrene-butadiene-styrene block copolymer, softening plasticizer, ethylene-methyl acrylate copolymer, silica, polymer silicone masterbatch, polyamide and phase The elastomeric material composed of melting agent is prepared by a specific formula ratio and preparation method, including water bath heating, magnetic stirring and ultraviolet photopolymerization, etc., to form a coordination crosslink network structure.

Benefits of technology

It significantly improves tensile performance, compressive resistance and wear resistance, extends the service life of wire at high and low temperatures, improves thermal stability and weather resistance, reduces usage costs and extends the service cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320543A_ABST
    Figure CN119320543A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of elastomer materials, and discloses an elastomer material of a drag chain wire rod, which is prepared from the following raw materials in percentage by weight: (1) 7-25% of copolymerized polypropylene; (2) 20%-40% of a hydrogenated styrene-butadiene-styrene block copolymer; (3) 10%-20% of a softening plasticizer; (4) 5%-10% of an ethylene-methyl acrylate copolymer; (5) 3%-5% of silicon dioxide (gas phase method); (6) 2-5% of polymer silicone master batch; (7) 8%-15% of polyamide; (8) 5%-10% of an intermiscible agent; the invention further discloses a preparation method of the elastomer material of the drag chain wire rod. The tensile property, the pressure resistance and the wear resistance of a wire made of the elastomer material provided by the invention are greatly improved compared with those of the prior art, and the phenomena of performance loss of the wire at a high temperature and cracking at a low temperature are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of elastomeric materials, and in particular to an elastomeric material for a drag chain wire and a preparation method thereof. Background Art

[0002] Elastomeric materials are a type of material that can return to its original shape after force is applied. They have special physical properties and can undergo reversible deformation when subjected to force, and return to their original state after the external force is removed. The main characteristics of elastomeric materials are their elastic modulus and resilience. The elastic modulus is a measure of the material's ability to resist deformation, that is, the material's ability to deform when subjected to force. Resilience refers to the material's ability to return to its original state after the external force is removed. With the increasing application of artificial intelligence and new energy, elastomeric wires are being used more and more in industry and life, and the requirements for the use of wires are also increasing.

[0003] Wires made of different materials are also uneven. Now mechanical drag chain wires are used more and more widely in various environments. For example, the amount of drag chain wires used in automated production equipment and artificial intelligence has increased dramatically. However, existing materials have many problems such as: not wear-resistant, low tensile strength, and excessive performance loss under high and low temperature differences.

[0004] Therefore, it is necessary to design an elastomeric material for a drag chain wire and a preparation method thereof to solve the above problems. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an elastomeric material for a drag chain wire and a preparation method thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] An elastomeric material for a drag chain wire, the elastomeric material being composed of the following raw material formulas in percentage by weight:

[0008] (1) Copolymer polypropylene 7% to 25%;

[0009] (2) 20% to 40% hydrogenated styrene-butadiene-styrene block copolymer;

[0010] (3) 10% to 20% softening plasticizer;

[0011] (4) 5% to 10% ethylene-methyl acrylate copolymer;

[0012] (5) Silicon dioxide (gas phase method) 3% to 5%;

[0013] (6) 2-5% polymer silicone masterbatch.

[0014] (7) Polyamide 8% to 15%

[0015] (8) Melting agent: 5% to 10%.

[0016] A method for preparing an elastomeric material for a drag chain wire, the preparation method is as follows:

[0017] (1) Weigh six portions of sodium polyacrylate with a molecular weight of 5100, with a mass of 0.5875 g (6.25 mmol based on the molar number of sodium carboxylate) and dissolve them in 25 mL of deionized water to prepare a 0.25 mol / L aqueous solution. The aqueous solution is allowed to stand for 6 h to allow the main chain of the sodium polyacrylate to fully dissolve and stretch. Weigh 1.7972 g (6.25 mmol) of ZnSO47H2O and dissolve it in 25 mL of deionized water to prepare a 0.25 mol / L aqueous solution. Heat the water bath at 28°C and stir magnetically, gradually drop the ZnSO47H2O aqueous solution into the PAA-Na aqueous solution. The addition is completed within 30 min, and the pH of the solution is adjusted to 6.0, 5.5, 5.0, 4.5, and 4.0, respectively. After reacting for 6 h, stirring is stopped to obtain a white solid product. The solid product is washed three times with deionized water and dried under vacuum at 55°C for 24 h to obtain a solid product, referred to as PAA-Zn. Zn in the solid product is 0. 2+ The content was determined by EDTA complexometric titration;

[0018] (2) A PAA-Na aqueous solution with a molecular weight of 3000 and a concentration of 0.25 mol / L was prepared. Based on the molar ratio of sodium carboxylate to Zn2* in PAA-Na being 1:1, a ZnSO,7H2O aqueous solution with a concentration of 0.25 mol / L was prepared. The volumes of both solutions were 25 mL. The ZnSO:7H2O aqueous solution was slowly added dropwise to the PAA-Na aqueous solution. The solution was heated in a water bath at 28°C with magnetic stirring. After 30 min, the addition was completed. The pH of the solution was adjusted to 6.0, 5.5, 5.0, 4.5, and 4.0, respectively. After reacting for 6 h, stirring was stopped to obtain a white solid product. The solid product was washed three times with deionized water and dried under vacuum at 55°C for 24 h to obtain a solid product. Zn 2 The content was determined by EDTA complexometric titration;

[0019] (3) Weigh 6 parts of sodium polyacrylate (6.25 mmol in terms of molar number of groups) with a mass of 0.5875 g and dissolve it in 25 mL of deionized water to prepare a 0.25 mol / L aqueous solution. Let it stand for 6 h to allow the polymer chain to fully dissolve and stretch. Weigh 1.7972 g of ZnSO:7H,O (6.25 mmol) and dissolve it in 25 mL of deionized water to prepare a 0.25 mol / L aqueous solution. Heat the solution in a water bath at 28°C and stir it with a magnetic stirrer. Slowly drop the zinc sulfate solution into the sodium polyacrylate solution for 30 min. After the addition is completed, adjust the pH of the solution to 6.0. Continue to react for 0 h, 3 h, 6 h, 9 h, 12 h, 15 h, and 18 h to obtain a white solid product. The solid product is washed three times with deionized water and dried in vacuo at 55°C for 24 h to obtain a solid product. The solid product contains Zn 2+ The content was determined by EDTA complexometric titration;

[0020] (4) Zn in the coordination cross-linking product 2+ Content determination: The pH value of the aqueous solution affects the configuration of the PAA-Na main chain and the reaction microenvironment. The zinc sulfate solution was slowly added to the sodium polyacrylate solution. After the addition was completed, the pH was adjusted to 6.0, 5.5, 5.0, 4.5, and 4.0 respectively. Stirring was stopped after 6 hours. When the pH value of the solution was 6.0, the PAA-Na main chain in the solution contained a large number of carboxyl anions, and the degree of ionization was about 42%. Under this pH condition, Zn 2+ It is easy to form coordination crosslinking within the polymer chain molecule and between the main chains with PAA-Na. The coordination crosslinking product is tightly agglomerated and gradually forms a white powder insoluble in water. When the solution pH is less than 4.5, the content of carboxyl anion groups on the PAA-Na main chain decreases, the carboxyl group increases, and the carboxyl group and Zn 2+ The ionic bond interaction between them is weak, and they cannot form a tight coordination cross-linking product, and only form a transparent colloid;

[0021] (5) Preparation of coordinated composite elastomer: The precursor liquid of the composite elastomer includes HEMA, HEA, MAA, PAA, urea, PEGDA-200, and photoinitiator 1173. The solvent is water and ethanol. The precursor liquid is colorless and transparent, indicating that the reaction raw materials have good compatibility. A certain volume of the precursor liquid is placed in a polytetrafluoroethylene mold for reaction. First, N 2 Under the protection of ultraviolet light, a colorless and transparent gel is formed for a period of time, that is, hydroxyethyl methacrylate-hydroxyethyl acrylate-methacrylic acid copolymer is formed, which plays a role in supporting the network structure. Secondly, after the mold is sealed, the reaction is heated at 85℃ for 12h, and the urea in the gel is gradually decomposed into NH3 and CO2. NH3 immediately reacts with H + Combined with NH4, the carboxyl group in polyacrylic acid is converted into carboxyl anion. 2+The coordination effect of polyacrylic acid and Zn 2+ The coordination cross-linking network is formed, and finally the solvent is removed to obtain a dry coordination composite elastomer. 2+ The molar ratios were 1:0.3, 1:0.4, 1:0.5, and 1:0.6, respectively, and polyacrylic acid-based coordination composite elastomers with corresponding molar ratios were prepared.

[0022] The present invention has the following beneficial effects:

[0023] 1. The tensile properties, compression resistance and wear resistance of the finished wire are greatly improved compared with before;

[0024] 2. Greatly improve the performance loss of wire at high temperature and cracking at low temperature;

[0025] 3. The thermal stability and weather resistance of the finished wire are significantly improved, effectively reducing the cost of use and increasing the service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a step diagram of a method for preparing an elastomeric material for a drag chain wire proposed by the present invention. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0028] An elastomeric material for a drag chain wire, the elastomeric material being composed of the following raw material formulas in percentage by weight:

[0029] (1) Copolymer polypropylene 7% to 25%;

[0030] (2) 20% to 40% hydrogenated styrene-butadiene-styrene block copolymer;

[0031] (3) 10% to 20% softening plasticizer;

[0032] (4) 5% to 10% ethylene-methyl acrylate copolymer;

[0033] (5) Silicon dioxide (gas phase method) 3% to 5%;

[0034] (6) 2-5% polymer silicone masterbatch.

[0035] (7) Polyamide 8% to 15%

[0036] (8) Melting agent: 5% to 10%.

[0037] Reference Figure 1, a method for preparing an elastomeric material for a drag chain wire, the preparation method is as follows:

[0038] (1) Weigh six portions of sodium polyacrylate with a molecular weight of 5100, with a mass of 0.5875 g (6.25 mmol based on the molar number of sodium carboxylate) and dissolve them in 25 mL of deionized water to prepare a 0.25 mol / L aqueous solution. The aqueous solution is allowed to stand for 6 h to allow the main chain of the sodium polyacrylate to fully dissolve and stretch. Weigh 1.7972 g (6.25 mmol) of ZnSO47H2O and dissolve it in 25 mL of deionized water to prepare a 0.25 mol / L aqueous solution. Heat the water bath at 28°C and stir magnetically, gradually drop the ZnSO47H2O aqueous solution into the PAA-Na aqueous solution. The addition is completed within 30 min, and the pH of the solution is adjusted to 6.0, 5.5, 5.0, 4.5, and 4.0, respectively. After reacting for 6 h, stirring is stopped to obtain a white solid product. The solid product is washed three times with deionized water and dried under vacuum at 55°C for 24 h to obtain a solid product, referred to as PAA-Zn. Zn in the solid product is 0. 2+ The content was determined by EDTA complexometric titration;

[0039] (2) Prepare a PAA-Na aqueous solution with a molecular weight of 3000 and a concentration of 0.25 mol / L. 2+ The molar ratio was 1:1, and the concentration of the prepared ZnSO, 7H2O aqueous solution was 0.25 mol / L. The volume of both was 25 mL. The ZnSO: 7H2O aqueous solution was slowly added dropwise to the PAA-Na aqueous solution, heated in a water bath at 28 °C and magnetically stirred. After 30 min, the addition was completed, and the pH of the solution was adjusted to 6.0, 5.5, 5.0, 4.5, and 4.0, respectively. After 6 h of reaction, stirring was stopped to obtain a white solid product. The solid product was washed three times with deionized water and dried in vacuum at 55 °C for 24 h to obtain a solid product. Zn 2 The content was determined by EDTA complexometric titration;

[0040] (3) Weigh 6 parts of sodium polyacrylate (6.25 mmol in terms of molar number of groups) with a mass of 0.5875 g and dissolve it in 25 mL of deionized water to prepare a 0.25 mol / L aqueous solution. Let it stand for 6 h to allow the polymer chain to fully dissolve and stretch. Weigh 1.7972 g of ZnSO:7H,O (6.25 mmol) and dissolve it in 25 mL of deionized water to prepare a 0.25 mol / L aqueous solution. Heat the solution in a water bath at 28°C and stir it with a magnetic stirrer. Slowly drop the zinc sulfate solution into the sodium polyacrylate solution for 30 min. After the addition is completed, adjust the pH of the solution to 6.0. Continue to react for 0 h, 3 h, 6 h, 9 h, 12 h, 15 h, and 18 h to obtain a white solid product. The solid product is washed three times with deionized water and dried in vacuo at 55°C for 24 h to obtain a solid product. The solid product contains Zn 2+ The content was determined by EDTA complexometric titration;

[0041] (4) Zn in the coordination cross-linking product 2+ Content determination: The pH value of the aqueous solution affects the configuration of the PAA-Na main chain and the reaction microenvironment. The zinc sulfate solution was slowly added to the sodium polyacrylate solution. After the addition was completed, the pH was adjusted to 6.0, 5.5, 5.0, 4.5, and 4.0 respectively. Stirring was stopped after 6 hours. When the pH value of the solution was 6.0, the PAA-Na main chain in the solution contained a large number of carboxyl anions, and the degree of ionization was about 42%. Under this pH condition, Zn 2+ It is easy to form coordination crosslinking within the polymer chain molecule and between the main chains with PAA-Na. The coordination crosslinking product is tightly agglomerated and gradually forms a white powder insoluble in water. When the solution pH is less than 4.5, the content of carboxyl anion groups on the PAA-Na main chain decreases, the carboxyl group increases, and the carboxyl group and Zn 2+ The ionic bond interaction between them is weak, and they cannot form a tight coordination cross-linking product, and only form a transparent colloid;

[0042] (5) Preparation of coordinated composite elastomer: The precursor liquid of the composite elastomer includes HEMA, HEA, MAA, PAA, urea, PEGDA-200, and photoinitiator 1173. The solvent is water and ethanol. The precursor liquid is colorless and transparent, indicating that the reaction raw materials have good compatibility. A certain volume of the precursor liquid is placed in a polytetrafluoroethylene mold for reaction. First, N 2 Under the protection of ultraviolet light, a colorless and transparent gel is formed for a period of time, that is, hydroxyethyl methacrylate-hydroxyethyl acrylate-methacrylic acid copolymer is formed, which plays a role in supporting the network structure. Secondly, after the mold is sealed, the reaction is heated at 85℃ for 12h, and the urea in the gel is gradually decomposed into NH3 and CO2. NH3 immediately reacts with H + Combined with NH4, the carboxyl group in polyacrylic acid is converted into carboxyl anion. 2+The coordination effect of polyacrylic acid and Zn 2+ The coordination cross-linking network is formed, and finally the solvent is removed to obtain a dry coordination composite elastomer. 2+ The molar ratios were 1:0.3, 1:0.4, 1:0.5, and 1:0.6, respectively, and polyacrylic acid-based coordination composite elastomers with corresponding molar ratios were prepared.

[0043] Performance comparison between this formula and previous formulas:

[0044] Our side in the past proportion 1.03g / cm3 0.98g / cm3 Tensile 16Mpa 9Mpa Elongation 550% 500% Number of drags 4.5 million times 2 million times High temperature test 150℃ No cracks No cracks Low temperature test -40℃ No break fracture

[0045] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An elastomeric material for a drag chain wire, characterized in that: The elastomer material is composed of the following raw material formula in weight percentage: (1) Copolymer polypropylene 7% to 25%; (2) 20% to 40% hydrogenated styrene-butadiene-styrene block copolymer; (3) 10% to 20% softening plasticizer; (4) 5% to 10% ethylene-methyl acrylate copolymer; (5) Silicon dioxide (gas phase method) 3% to 5%; (6) 2-5% polymer silicone masterbatch. (7) Polyamide 8% to 15%; (8) Melting agent: 5% to 10%.

2. A method for preparing an elastomeric material for a drag chain wire, characterized in that: The preparation method is as follows: (1) Weigh six portions of sodium polyacrylate with a molecular weight of 5100, with a mass of 0.5875 g (6.25 mmol based on the molar number of sodium carboxylate) and dissolve them in 25 mL of deionized water to prepare a 0.25 mol / L aqueous solution. The aqueous solution is allowed to stand for 6 h to allow the main chain of the sodium polyacrylate to fully dissolve and stretch. Weigh 1.7972 g (6.25 mmol) of ZnSO47H2O and dissolve it in 25 mL of deionized water to prepare a 0.25 mol / L aqueous solution. Heat the water bath at 28°C and stir magnetically, gradually drop the ZnSO47H2O aqueous solution into the PAA-Na aqueous solution. The addition is completed within 30 min, and the pH of the solution is adjusted to 6.0, 5.5, 5.0, 4.5, and 4.0, respectively. After reacting for 6 h, stirring is stopped to obtain a white solid product. The solid product is washed three times with deionized water and dried under vacuum at 55°C for 24 h to obtain a solid product, referred to as PAA-Zn. Zn in the solid product is 0. 2+ The content was determined by EDTA complexometric titration; (2) A PAA-Na aqueous solution with a molecular weight of 3000 and a concentration of 0.25 mol / L was prepared. Based on the molar ratio of sodium carboxylate to Zn2* in PAA-Na being 1:1, a ZnSO,7H2O aqueous solution with a concentration of 0.25 mol / L was prepared. The volumes of both solutions were 25 mL. The ZnSO:7H2O aqueous solution was slowly added dropwise to the PAA-Na aqueous solution. The solution was heated in a water bath at 28°C with magnetic stirring. After 30 min, the addition was completed. The pH of the solution was adjusted to 6.0, 5.5, 5.0, 4.5, and 4.0, respectively. After reacting for 6 h, stirring was stopped to obtain a white solid product. The solid product was washed three times with deionized water and dried under vacuum at 55°C for 24 h to obtain a solid product. Zn 2 The content was determined by EDTA complexometric titration; (3) Weigh 6 parts of sodium polyacrylate (6.25 mmol in terms of molar number of groups) with a mass of 0.5875 g and dissolve it in 25 mL of deionized water to prepare a 0.25 mol / L aqueous solution. Let it stand for 6 h to allow the polymer chain to fully dissolve and stretch. Weigh 1.7972 g of ZnSO:7H,O (6.25 mmol) and dissolve it in 25 mL of deionized water to prepare a 0.25 mol / L aqueous solution. Heat the solution in a water bath at 28°C and stir it with a magnetic stirrer. Slowly drop the zinc sulfate solution into the sodium polyacrylate solution for 30 min. After the addition is completed, adjust the pH of the solution to 6.

0. Continue to react for 0 h, 3 h, 6 h, 9 h, 12 h, 15 h, and 18 h to obtain a white solid product. The solid product is washed three times with deionized water and dried in vacuo at 55°C for 24 h to obtain a solid product. The solid product contains Zn 2+ The content was determined by EDTA complexometric titration; (4) Zn in the coordination cross-linking product 2+ Content determination: The pH value of the aqueous solution affects the configuration of the PAA-Na main chain and the reaction microenvironment. The zinc sulfate solution was slowly added to the sodium polyacrylate solution. After the addition was completed, the pH was adjusted to 6.0, 5.5, 5.0, 4.5, and 4.0 respectively. Stirring was stopped after 6 hours. When the pH value of the solution was 6.0, the PAA-Na main chain in the solution contained a large number of carboxyl anions, and the degree of ionization was about 42%. Under this pH condition, Zn 2+ It is easy to form coordination crosslinking within the polymer chain molecule and between the main chains with PAA-Na. The coordination crosslinking product is tightly agglomerated and gradually forms a white powder insoluble in water. When the solution pH is less than 4.5, the content of carboxyl anion groups on the PAA-Na main chain decreases, the carboxyl group increases, and the carboxyl group and Zn 2+ The ionic bond interaction between them is weak, and they cannot form a tight coordination cross-linking product, and only form a transparent colloid; (5) Preparation of coordinated composite elastomer: The precursor liquid of the composite elastomer includes HEMA, HEA, MAA, PAA, urea, PEGDA-200, and photoinitiator 1173. The solvent is water and ethanol. The precursor liquid is colorless and transparent, indicating that the reaction raw materials have good compatibility. A certain volume of the precursor liquid is placed in a polytetrafluoroethylene mold for reaction. First, N 2 Under the protection of ultraviolet light, a colorless and transparent gel is formed for a period of time, that is, hydroxyethyl methacrylate-hydroxyethyl acrylate-methacrylic acid copolymer is formed, which plays a role in supporting the network structure. Secondly, after the mold is sealed, the reaction is heated at 85℃ for 12h, and the urea in the gel is gradually decomposed into NH3 and CO2. NH3 immediately reacts with H + Combined with NH4, the carboxyl group in polyacrylic acid is converted into carboxyl anion. 2+ The coordination effect of polyacrylic acid and Zn 2+ The coordination forms a coordination cross-linking network, and finally the solvent is removed to obtain a dry coordination composite elastomer. 2+ The molar ratios were 1:0.3, 1:0.4, 1:0.5, and 1:0.6, respectively, and polyacrylic acid-based coordinated composite elastomers with corresponding molar ratios were prepared.